Halal Computer Systems Validation Quality Assurance, Risk Assessment and Regulatory Compliance For The Pharmaceutical and Healthcare Industry - Raja Ikram, Raja Rina; Abd Ghani, M. K.; Abd. Samad, Hasan Basari (2012)
This research aims to develop a framework to address halal regulatory industry requirements for computer validation in the pharmaceutical and healthcare industry. Computer Validation is a regulatory pharmaceutical industry requirement to produce documented evidence that all computerized systems are qualified and validated to demonstrate their ability for intended use. This paper examines the processes involved to comply with the Halal Pharmaceuticals Guidelines from a technology point of view by identifying processes involved in the pharmaceutical supply chain and common computerized systems used to support it. The haram critical control points shall also be established based on a systematic approach to determine the key process points that determine the validity of the halal state. A risk analysis of controls and validation required from the technology perspective shall be proposed for the critical points identified. These controls shall then be harmonized with the current international regulatory standards for computerized systems validation to propose a standard framework and guideline for the usage of computerized systems for halal compliance throughout the pharmaceutical supply chain. The Malaysian Halal Pharmaceuticals Guideline shall be the baseline reference of halal compliance standards throughout this research.